IMPLEMENTATION OF THE “GOLDEN RULE” IN THE FISCAL MECHANISM FOR REGULATING INVESTMENT PROCESSES IN UKRAINE - RUDENKO, Victoriia (Scientific journal «World of Finance», 2023)
Introduction. After the global financial and economic crisis, which led to the deterioration of fiscal stability, the growth of the budget deficit and public debt in many countries, ensuring the quality and long-term sustainability of public finances is one of the priority areas of fiscal policy. In this context, the implementation of the “golden rule” becomes especially relevant. Such a rule makes it possible to release state investments from the corresponding target indicators of the budget deficit. Accordingly, fiscal policy is being modernized, which will provide more opportunities for budgetary maneuvering and public investment.The purpose of the article is to reveal the content, advantages and disadvantages, as well as the peculiarities of the implementation of the “golden rule” in the fiscal mechanism for regulating investment processes in Ukraine.Results. It was found that the “golden rule” provides for public borrowing only for the purpose of investing in projects that will pay off in the future, as well as financing current budget expenditures at the expense of taxation. The advantages and disadvantages of the implementation of the “golden rule” in the fiscal mechanism for regulating investment processes are determined. Modified versions of the “golden rule” are considered: the “limited golden rule” proposed by the European Fiscal Council and the “asymmetric golden rule” substantiated by scientists. The ways of introducing the “golden rule” into domestic fiscal practice are outlined.Conclusions. The need to implement the “golden rule” into the fiscal mechanism for regulating investment processes in Ukraine is clarified. The creation of the Agency for State Investment Management in the context of the “golden rule” is substantiated. It is proposed to apply a more flexible approach to the formation of the budget deficit in the transitional post-war period before the full implementation of the “golden rule” in Ukraine. It is advisable to direct further scientific research to the search for alternative options for increasing the efficiency of public investments under the conditions of compliance with fiscal stability.